Lithium iron phosphate dopant and preparation method and application thereof
By preparing lithium iron phosphate dopants with high specific surface area and optimized structure, the problem of compaction density and capacity of lithium iron phosphate battery materials is solved, and its performance in solid-state batteries is significantly improved.
Patent Information
- Application Number
- CN202411846333.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-18
AI Technical Summary
The compaction density and capacity of existing lithium iron phosphate battery materials are low, which affects its application in solid-state batteries.
By preparing a new lithium iron phosphate dopant, the pH value is adjusted to 1.5-2.5 by combining titanium salt solution, phosphate solution and ammonium salt solution, the pH value is adjusted to 1.5-2.5, and titanium phosphate precipitate is formed, and mixed and nano-deployed with lithium source, phosphorus source, fluorine source and reducing agent. After calcination reduction and alkali erosion treatment, lithium iron phosphate dopant with high specific surface area and optimized structure is obtained.
The compaction density and capacity of lithium iron phosphate material are improved, its performance at low temperatures is enhanced, better doping effect and ion diffusion are achieved, and the energy density and cycle life of the battery are improved.
Smart Images

Figure CN119650701A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery materials, and in particular to a lithium iron phosphate dopant and a preparation method and application thereof. Background Art
[0002] As the global demand for clean energy and sustainable energy solutions continues to grow, the market demand for lithium-ion batteries as an efficient and environmentally friendly energy storage device has increased rapidly. Lithium iron phosphate batteries have been widely used in electric vehicles, energy storage systems and portable electronic devices due to their high safety, long life and environmental friendliness.
[0003] Lithium iron phosphate dopants are used in lithium iron phosphate battery materials to effectively improve the electrochemical properties of the materials, increase the energy density and cycle life of the battery. At present, conventional dopants usually hinder the growth of lithium iron phosphate particles, resulting in low compaction density and poor capacity of the lithium iron phosphate material produced.
[0004] Therefore, developing a new preparation method for lithium iron phosphate dopants to overcome the defects in the prior art and improve the electrochemical properties of the material, especially the compaction density and capacity, is of great significance for promoting the application of lithium iron phosphate in solid-state battery materials. Summary of the invention
[0005] In view of the technical problems existing in the background technology, the present application provides a lithium iron phosphate dopant and a preparation method and application thereof, aiming to solve the technical problems of low compaction density and capacity of lithium iron phosphate materials.
[0006] In a first aspect, an embodiment of the present application provides a method for preparing a lithium iron phosphate dopant, comprising the following steps:
[0007] Adding a phosphate solution and an ammonium salt solution to a titanium salt solution, adjusting the pH value of the solution to 1.5-2.5, and obtaining a precipitate;
[0008] A phosphorus source, a lithium source, a fluorine source and a reducing agent are added to the precipitate to obtain a mixture, and then the mixture is slurried, dispersed, dried and calcined in sequence to obtain a calcined product;
[0009] Alkali solution is added to the calcined product, and the product is boiled, filtered, washed and dried to obtain a lithium iron phosphate dopant.
[0010] In the technical solution of the embodiment of the present application, a titanium phosphate precipitate of tetravalent titanium is first prepared, and mixed and nanosized with a lithium source, a phosphorus source, a fluorine source and a reducing agent, and then calcined and reduced, so that both a redox reaction and a solid phase reaction occur. At the same time, the introduction of fluorine allows the prepared lithium iron phosphate dopant to effectively improve the electronegativity of the lithium iron phosphate material, and because the dual doping of anions and cations is achieved, its ionic conductivity can also be improved.
[0011] Among them, by adjusting the pH value, it is conducive to forming a stable precipitate, that is, the condition of low pH value is conducive to the precipitation of metal ions in the form of phosphate. Alkali solution is added to the calcined material, and holes can be formed on the surface of the calcined material through the erosion of the alkali solution, that is, the BET specific surface area of the prepared lithium iron phosphate dopant can be effectively increased, so that the reaction activity of the prepared lithium iron phosphate dopant can be effectively increased, and the lithium iron phosphate dopant has a better doping effect on the lithium iron phosphate material. At the same time, ion diffusion can be better achieved during the solid phase reaction. Therefore, the lithium iron phosphate dopant prepared in the present application can effectively improve the compaction density of the lithium iron phosphate material, avoid the low compaction density caused by the conventional dopant hindering the growth of lithium iron phosphate particles, and at the same time, the lithium iron phosphate dopant of the present application has a certain capacity, which can release the capacity at low voltage, thereby effectively improving the technical problem of low capacity of the lithium iron phosphate material.
[0012] In some embodiments, the concentrations of the titanium salt solution and the phosphate solution are both 1-2 mol / L; and / or, the molar ratio of the titanium salt contained in the titanium salt solution to the phosphate contained in the phosphate solution is 3:(4.05-4.1).
[0013] In this embodiment, by precisely controlling the concentration and molar ratio of the titanium salt and the phosphate, a precipitate with uniform purity and particle size distribution can be obtained, thereby improving the purity of the final lithium iron phosphate dopant. At the same time, a specific molar ratio helps to achieve an optimized ratio of elements such as titanium, phosphorus, and lithium, thereby improving the crystal structure and electrochemical properties of lithium iron phosphate.
[0014] In some embodiments, the titanium salt contained in the titanium salt solution is at least one of titanyl sulfate and titanium tetrachloride; and / or the phosphate contained in the phosphate solution is one or more of ammonium phosphate, sodium phosphate, ammonium monohydrogen phosphate, sodium monohydrogen phosphate, ammonium dihydrogen phosphate and sodium dihydrogen phosphate.
[0015] In this embodiment, the use of specific titanium salts and phosphates can reduce the introduction of impurities, thereby improving the purity of the lithium iron phosphate dopant. At the same time, the specific titanium salts and phosphates can form a structure in the lithium iron phosphate lattice that is more conducive to electron migration, thereby improving the electrochemical stability of the material.
[0016] In some embodiments, the concentration of the ammonium salt solution is 0.1-1 mol / L; and / or the ammonium salt contained in the ammonium salt solution is at least one of ammonium carbonate and ammonium bicarbonate.
[0017] In this embodiment, the ammonium salt solution can provide suitable reaction conditions, which helps to control the precipitation formation rate, so as to obtain the desired particle size and morphology. Among them, ammonium carbonate and ammonium bicarbonate will partially dissociate in water to generate ammonia, which helps to adjust the pH value of the solution, control the precipitation formation process, and then help to form a uniform and stable precipitation. Understandably, due to the high uniformity and purity of the precipitate, it has better processing performance in subsequent processing, such as easier to slurry, grind, dry and calcined.
[0018] In some embodiments, the molar ratio of the precipitate, the phosphorus source, the lithium source and the fluorine source is 1:(2.05-2.2):(1.4-1.6):(0.05-0.1); and / or the phosphorus source is at least one of lithium phosphate and lithium dihydrogen phosphate; and / or the lithium source is at least one of lithium carbonate and lithium hydroxide; and / or the fluorine source is lithium fluoride; and / or the molar ratio of the reducing agent to titanium in the precipitate is 1:(0.5-2); and / or the reducing agent is at least one of carbon, oxalic acid, citric acid, ascorbic acid and glucose.
[0019] In this embodiment, by precisely controlling the molar ratio of each element, a lithium iron phosphate dopant with a desired chemical composition can be obtained. Understandably, by precisely controlling the chemical composition, the microstructure of the dopant can be optimized, thereby improving its application performance in lithium iron phosphate materials. Among them, the introduction of phosphorus can coarsen the grains, increase the compaction density, and improve the structural stability of the lithium iron phosphate material; the introduction of fluorine can increase the electronegativity of the final lithium iron phosphate, and can also improve the ionic conductivity of the lithium iron phosphate material; the introduction of titanium can improve the electron transmission path inside the lithium iron phosphate material and help maintain the stability of the crystal structure; lithium is one of the main components of lithium iron phosphate materials, and the content and state of lithium affect the electrochemical properties of the material. Increasing the content of lithium can increase the theoretical specific capacity of the lithium iron phosphate material. Therefore, by doping these elements, the lattice structure and electronic conductivity of the lithium iron phosphate material can be improved, the compaction density and capacity can be improved, which helps to maintain a good ion diffusion rate at low temperatures and improve the low temperature performance of the lithium iron phosphate material.
[0020] In some embodiments, the slurrying method is: adding water to the mixture to slurry so that the solid content is 30-40wt%; and / or, the dispersion method is: grinding the slurried material until the particle size of the material is 200-400nm; and / or, the drying method is: spray drying the ground material to obtain a dry material with a particle size of 5-25μm and a moisture content of less than 1.5wt%; and / or, the calcination method is: calcining the dry material at 600-750°C for 6-12h.
[0021] In this embodiment, slurrying helps to evenly disperse the mixture, preparing for the subsequent dispersion and drying processes; dispersion can further refine the material and increase its specific surface area, which is beneficial to improving the electrochemical performance; spray drying can quickly remove moisture while maintaining the particle size distribution of the material, which is beneficial to the subsequent calcination process; calcination helps to form a stable crystal form, improve the structural stability of the material, and remove residual organic matter and impurities.
[0022] In some embodiments, the alkali solution is one of potassium hydroxide solution, lithium hydroxide solution and sodium hydroxide solution, and the concentration is 0.1-0.5 mol / L; and / or the mass ratio of the calcined product to the alkali solution is 1:(1-2); the cooking temperature is 100-110° C., and the cooking time is 15-30 min.
[0023] In this embodiment, some holes can be formed on the surface of the calcined product by alkali corrosion, thereby effectively increasing the BET specific surface area of the prepared lithium iron phosphate dopant, and further increasing the reaction activity of the prepared lithium iron phosphate dopant.
[0024] In a second aspect, an embodiment of the present application provides a lithium iron phosphate dopant, which is obtained by the preparation method of the lithium iron phosphate dopant provided in the first aspect of the present application, and the prepared lithium iron phosphate dopant has a particle size of 0.5 to 5.0 μm and a BET specific surface area of 20 to 30 m 2 / g.
[0025] In the technical solution of the embodiment of the present application, the lithium iron phosphate dopant has a smaller particle size and a larger specific surface area, which can improve the reaction activity, thereby achieving a better doping effect. In the solid-phase reaction process of preparing lithium iron phosphate, ion diffusion can be better carried out, and the capacity and compaction density of lithium iron phosphate can be effectively improved, and the performance of lithium iron phosphate at low temperatures can be improved.
[0026] In a third aspect, an embodiment of the present application provides a lithium iron phosphate positive electrode material, which is prepared by solid phase reaction of the lithium iron phosphate dopant provided in the second aspect of the present application with iron phosphate, a lithium source and a carbon source.
[0027] In this embodiment, the lithium iron phosphate positive electrode material to which the lithium iron phosphate dopant is added has the advantages of high compaction density, high capacity, and excellent low-temperature performance.
[0028] In a fourth aspect, an embodiment of the present application provides a positive electrode plate, comprising the lithium iron manganese phosphate positive electrode material provided in the third aspect of the present application.
[0029] In this embodiment, the positive electrode plate contains the above-mentioned lithium iron phosphate positive electrode material, and thus has the advantages of high compaction density, high capacity, and excellent low-temperature performance.
[0030] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the technical solution of the present application, the following is a brief introduction to the drawings used in the present application. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0032] Figure 1 A flow chart of a method for preparing a lithium iron phosphate dopant provided in an embodiment of the present application;
[0033] Figure 2 This is a SEM image of the lithium iron phosphate dopant obtained in Example 1 of the present application. DETAILED DESCRIPTION
[0034] The following embodiments of the technical solution of the present application are described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.
[0035] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.
[0036] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.
[0037] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0038] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of the associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.
[0039] In the description of the embodiments of the present application, the term "multiple" refers to more than two (including two). Similarly, "multiple groups" refers to more than two groups (including two groups), and "multiple pieces" refers to more than two pieces (including two pieces).
[0040] Lithium iron phosphate dopants are used in lithium iron phosphate battery materials to effectively improve the electrochemical properties of the materials, increase the energy density and cycle life of the battery. At present, conventional dopants usually hinder the growth of lithium iron phosphate particles, resulting in low compaction density and poor capacity of the prepared lithium iron phosphate cathode material.
[0041] In order to solve the technical problems of low compaction density and capacity of lithium iron phosphate positive electrode materials, the present application provides a lithium iron phosphate dopant and its preparation method and application, wherein, by first preparing a titanium phosphate precipitate of tetravalent titanium, then mixing and nano-forming it with a lithium source, a phosphorus source, a fluorine source and a reducing agent, and then calcining, reducing and alkali corroding it, the performance of the lithium iron phosphate dopant can be optimized, the specific surface area and reaction activity can be increased, and a better doping effect can be achieved, thereby achieving the technical effect of promoting the uniform growth of lithium iron phosphate particles and improving the compaction density and capacity of the material, and thus the compaction density and capacity performance of the positive electrode sheet can also be improved.
[0042] In a first aspect, the present invention provides a method for preparing a lithium iron phosphate dopant. Figure 1 As shown, the preparation method comprises the following steps:
[0043] S1. Adding a phosphate solution and an ammonium salt solution to a titanium salt solution, adjusting the pH value of the solution to 1.5-2.5, and obtaining a precipitate;
[0044] S2, adding a phosphorus source, a lithium source, a fluorine source and a reducing agent to the precipitate to obtain a mixture, and then sequentially slurrying, dispersing, drying and calcining the mixture to obtain a calcined product;
[0045] S3. Adding alkali solution to the calcined product, and obtaining lithium iron phosphate dopant through steaming, filtering, washing and drying.
[0046] In this embodiment, a titanium phosphate precipitate of tetravalent titanium is generated by chemical reaction, and adjusting the pH value to 1.5-2.5 can promote the reaction between the titanium salt and the phosphate to form the desired precipitate. Within this pH range, the precipitation efficiency of the metal ions can be optimized to ensure the formation of a uniform precipitate with the desired crystal form, reduce the co-precipitation of impurities, and improve the purity of the final product. If at a higher pH value, the metal ions will undergo a hydrolysis reaction, resulting in the structure and properties of the precipitate being affected, while at too low a pH value, it will cause unnecessary side reactions, such as redox reactions or reactions between other ions, reducing the purity of the target product. Specifically, the reaction solution can be stirred at 30-60°C for 1-2 hours to ensure that the reaction is fully carried out, thereby obtaining the desired titanium phosphate precipitate.
[0047] Furthermore, in this embodiment, the addition of a phosphorus source, a lithium source, a fluorine source and a reducing agent can change the chemical composition of the lithium iron phosphate dopant, the slurrying, dispersion, drying and calcination treatments can improve the microstructure and crystal morphology of the material, the addition of alkaline solution can erode some holes on the surface of the material, increase the BET specific surface area of the material, and the final form of the lithium iron phosphate dopant is obtained through filtration, washing and drying.
[0048] Furthermore, in some embodiments, the concentrations of the titanium salt solution and the phosphate solution are both 1-2 mol / L; and / or, the molar ratio of the titanium salt contained in the titanium salt solution to the phosphate contained in the phosphate solution is 3:(4.05-4.1).
[0049] In the technical solution of the embodiment of the present application, the setting of the ratio of titanium salt to phosphate can ensure the complete reaction while avoiding the occurrence of side reactions, thereby obtaining a product with excellent purity and performance. Specifically, the molar ratio of titanium salt to phosphate can be 3:4.05, 3:4.06, 3:4.07, 3:4.08, 3:4.09, 3:4.10 or any value in the range of 3:(4.05-4.1). Among them, ammonium salt helps adjust the pH value and promotes the formation of precipitation. At lower pH values, the reaction tends to generate particles with smaller particle size.
[0050] Furthermore, in some embodiments, the titanium salt contained in the titanium salt solution is at least one of titanyl sulfate and titanium tetrachloride; the phosphate contained in the phosphate solution is one or more of ammonium phosphate, sodium phosphate, ammonium monohydrogen phosphate, sodium monohydrogen phosphate, ammonium dihydrogen phosphate and sodium dihydrogen phosphate.
[0051] In this embodiment, the use of specific titanium salts and phosphates can reduce the introduction of impurities, thereby improving the purity of the lithium iron phosphate dopant. At the same time, the specific titanium salts and phosphates can form a structure in the lithium iron phosphate lattice that is more conducive to electron migration, thereby improving the electrochemical stability of the material.
[0052] Furthermore, in some embodiments, the concentration of the ammonium salt solution is 0.1-1 mol / L; and / or the ammonium salt contained in the ammonium salt solution is at least one of ammonium carbonate and ammonium bicarbonate.
[0053] In this embodiment, the ammonium salt solution can provide suitable reaction conditions, which helps to control the precipitation formation rate, so as to obtain the desired particle size and morphology. Among them, ammonium carbonate and ammonium bicarbonate will partially dissociate in water to generate ammonia, which helps to adjust the pH value of the solution, control the precipitation formation process, and then help to form a uniform and stable precipitation. Understandably, due to the high uniformity and purity of the precipitate, it has better processing performance in subsequent processing, such as easier to slurry, grind, dry and calcined.
[0054] Further, in some embodiments, the molar ratio of the precipitate, the phosphorus source, the lithium source and the fluorine source is 1:(2.05-2.2):(1.4-1.6):(0.05-0.1); and / or the phosphorus source is at least one of lithium phosphate and lithium dihydrogen phosphate; and / or the lithium source is at least one of lithium carbonate and lithium hydroxide; and / or the fluorine source is lithium fluoride; and / or the molar ratio of the reducing agent to titanium in the precipitate is 1:(0.5-2); and / or the reducing agent is one of carbon, oxalic acid, citric acid, ascorbic acid and glucose.
[0055] In the technical solution of the embodiment of the present application, the addition of a phosphorus source and a lithium source helps to stabilize the chemical state of iron and lithium to form a stable lithium iron phosphate structure. The addition of a fluorine source can improve the electronic structure of lithium iron phosphate by lattice doping, thereby improving its conductivity and electrochemical activity. The addition of a reducing agent can promote the reduction of metal ions and ensure the formation of the desired chemical phase during the calcination process. At the same time, by controlling the molar ratio of the raw materials, the crystal form of lithium iron phosphate can be affected to a certain extent, thereby optimizing its physical and chemical properties. Through these steps, a lithium iron phosphate dopant with optimized structure and performance can be prepared.
[0056] Specifically, the molar ratio of the precipitate, the phosphorus source, the lithium source and the fluorine source can be 1:2.05:1.4:0.05, 1:2.09:1.5:0.08, 1:2.20:1.6:0.10 or any value in the range of 1:(2.05-2.2):(1.4-1.6):(0.05-0.1). The molar ratio of the reducing agent to the titanium in the precipitate can be 1:0.5, 1:0.9, 1:1, 1:1.5, 1:2 or any value in the range of 1:(0.5-2).
[0057] Furthermore, in some embodiments, the slurrying method is: adding water to the mixture to slurry so that the solid content is 30-40wt%; the dispersion method is: grinding the slurried material until the particle size of the material is 200-400nm; the drying method is: spray drying the ground material to obtain a dry material with a particle size of 5-25μm and a moisture content of less than 1.5wt%; the calcination method is: calcining the dry material at 600-750°C for 6-12h, while introducing nitrogen for protection.
[0058] In the present application, slurrying can make the solid particles disperse evenly in the liquid to form a stable suspension. By adjusting the solid content, the viscosity and fluidity of the suspension can be controlled, which is helpful for the subsequent grinding process. Preferably, a solid content of 30 to 40 wt% can usually provide suitable suspension properties, which is neither too thin nor too viscous. At the same time, grinding can reduce the size of the solid particles and increase the specific surface area, thereby improving the reaction activity and the final doping effect. Preferably, a particle size range of 200 to 400 nm can provide a higher specific surface area and avoid the agglomeration problem caused by excessive grinding.
[0059] Furthermore, spray drying is a method of atomizing the material through a sprayer, contacting it with hot air in a drying chamber, and rapidly evaporating the water to obtain a dry powder. Preferably, a particle size of 5 to 25 μm helps to ensure that the material has good fluidity and dispersibility, and a water content of less than 1.5 wt% ensures the stability of the material during the subsequent calcination process. Among them, the temperature range of 600 to 750 ° C is to promote the chemical reaction in the material while avoiding the degradation of the material properties caused by excessively high temperatures; the calcination time of 6 to 12 hours can ensure that the reaction is fully carried out and help to form a uniform and stable structure; and the introduction of nitrogen during the calcination process can prevent the material from being oxidized at high temperatures, maintain the stability of the material components and improve the purity of the final product.
[0060] Furthermore, in some embodiments, the alkali solution is one of potassium hydroxide solution, lithium hydroxide solution and sodium hydroxide solution, and the concentration is 0.1-0.5 mol / L; and / or the mass ratio of the calcined product to the alkali solution is 1:(1-2); and / or the cooking temperature is 100-110° C., and the cooking time is 15-30 min.
[0061] In the present application, the alkaline solution can corrode the surface of the calcined material to remove impurities and part of the layered structure on the surface of the calcined material, thereby exposing more active sites and increasing the specific surface area of the calcined material. By removing some substances, more pores will be formed inside the calcined material. These pores can serve as paths for lithium ion transmission and increase the ion diffusion rate.
[0062] The mass ratio of the calcined product to the alkali solution can be 1:1, 1:2 or any value in the range of 1:(1-2). The cooking temperature can be 100°C, 105°C, 110°C or any value in the range of 100-110°C. The high temperature environment of the cooking process helps to accelerate the reaction of the alkali solution and the calcined product and improve the processing efficiency. The temperature range of 100-110°C can ensure the reaction rate without being too high to cause damage to the structure of the calcined product.
[0063] In a second aspect, the present invention provides a lithium iron phosphate dopant, which is prepared by the preparation method of the lithium iron phosphate dopant of the first aspect, wherein the particle size of the lithium iron phosphate dopant is 0.5 to 5.0 μm, and the BET specific surface area is 20 to 30 m 2 / g.
[0064] Among them, smaller particle size can provide a larger specific surface area, thereby increasing the contact area, improving the lithium ion transmission rate and material utilization. Understandably, BET specific surface area is an important parameter to measure the surface properties of materials, which reflects the number of active sites in the material; a higher specific surface area means more active sites for lithium ion embedding and extraction, which may improve the capacity and cycle performance of the material.
[0065] In a third aspect, an embodiment of the present application provides a lithium iron phosphate positive electrode material, which is prepared by a solid phase reaction between the lithium iron phosphate dopant of the second aspect and iron phosphate, a lithium source and a carbon source.
[0066] The lithium iron phosphate positive electrode material of the present application is prepared from the above-mentioned lithium manganese iron phosphate dopant, and thus has the advantages of high compaction density, high capacity, and excellent low-temperature performance.
[0067] Furthermore, in some embodiments, the mass ratio of the lithium iron phosphate dopant to the iron phosphate, the lithium source and the carbon source is (0.04-0.06):1:(0.2-0.3):(0.1-0.2).
[0068] In the technical solution of the embodiment of the present application, the addition of lithium iron phosphate dopant can optimize the electrochemical properties of the positive electrode material, thereby improving the energy density of the secondary battery prepared using the positive electrode material. Among them, the elements in the lithium iron phosphate dopant can enter the lattice of lithium iron phosphate to form a solid solution or a heterogeneous structure, thereby changing the electronic structure and physicochemical properties of the lithium iron phosphate positive electrode material. By precisely controlling the mass ratio of the lithium iron phosphate dopant to iron phosphate, lithium source and carbon source, the optimal synergistic effect between the components can be ensured, thereby achieving the optimization of the performance of the lithium iron phosphate positive electrode material. Specifically, the mass ratio of the lithium iron phosphate dopant to iron phosphate, lithium source and carbon source can be 0.04:1:0.2:0.1, 0.05:1:0.235:0.165, 0.06:1:0.3:0.2 or any value in the range of (0.04~0.06):1:(0.2~0.3):(0.1~0.2).
[0069] Further, in some embodiments, the lithium source is lithium carbonate; and / or the carbon source is selected from one or more of glucose, sucrose, fructose, cellulose, starch, citric acid, polyacrylic acid, polyethylene glycol and dopamine.
[0070] In the technical solution of the embodiment of the present application, the selected carbon source can be carbonized to form a conductive network during the high temperature treatment process, which helps to improve the electronic conductivity of the lithium iron phosphate material, thereby improving the charge and discharge performance of the secondary battery prepared using the lithium iron phosphate material. The carbon coating formed by the carbon source on the surface of the material can protect the lithium iron phosphate particles and prevent them from agglomeration and structural degradation during the cycle. The porous carbon structure facilitates the rapid diffusion of lithium ions, thereby improving the power density of the lithium iron phosphate positive electrode material. At the same time, the carbon coating can inhibit the precipitation of lithium at high temperatures, thereby maintaining the structural stability and electrochemical properties of the lithium iron phosphate positive electrode material.
[0071] Furthermore, in some embodiments, the lithium iron phosphate dopant is slurried with iron phosphate, a lithium source and a carbon source with water so that the solid content is 30-40 wt %, ground to a particle size of 200-400 nm, spray-dried to a particle size of 10-30 μm and a moisture content of less than 1.5 wt %, and then calcined at a temperature of 800-850° C. for 8-10 h while introducing nitrogen for protection.
[0072] In the technical solution of the embodiment of the present application, the lithium iron phosphate dopant is slurried with iron phosphate, lithium source and carbon source with water so that the solid content is 30-40wt%, which helps to evenly mix the components and provide a suitable material form for the subsequent grinding and drying steps. Grinding the slurry to a particle size of 200-400nm can significantly increase the specific surface area of the material, increase the contact area between the active substances, and help improve the electrochemical activity of the material. The particle size distribution of the material obtained by spray drying is 10-30μm, which is conducive to improving the compaction density of the material, thereby improving the energy density of the battery. By spray drying, the moisture content of the material is reduced to less than 1.5wt%, which can reduce the evaporation of water during high-temperature calcination and avoid the destruction of the material structure. High-temperature calcination helps to form a stable crystal structure and improve the overall performance of the material. Introducing nitrogen during the calcination process can prevent the material from being oxidized at high temperatures and maintain the chemical stability of the material.
[0073] In a fourth aspect, an embodiment of the present application provides a positive electrode plate, comprising the lithium iron phosphate positive electrode material of the third aspect.
[0074] The positive electrode plate of the present application includes the above-mentioned lithium iron manganese phosphate positive electrode material, and thus has the advantages of high compaction density, high capacity, and excellent low-temperature performance.
[0075] Some specific embodiments are listed below. It should be noted that the embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used without specifying the manufacturer are all conventional products that can be obtained commercially.
[0076] 1. Preparation method
[0077] Example 1
[0078] This embodiment provides a method for preparing a lithium iron phosphate dopant, comprising the following steps:
[0079] Add ammonium monohydrogen phosphate solution and ammonium bicarbonate solution to the titanyl sulfate solution, adjust the pH of the solution to 2.0, and stir the reaction at 45°C for 1.5 hours to obtain a precipitate; the molar ratio of titanyl sulfate to ammonium monohydrogen phosphate is 3:4.08, the concentration of the ammonium bicarbonate solution is 0.5 mol / L, and the concentrations of the titanyl sulfate solution and the ammonium monohydrogen phosphate solution are both 1.5 mol / L.
[0080] Lithium phosphate, lithium carbonate and lithium fluoride are added to the precipitate, and then a reducing agent is added to obtain a mixture, wherein the molar ratio of the precipitate, lithium phosphate, lithium carbonate and lithium fluoride is 1:2.09:1.5:0.08, the reducing agent is amorphous carbon, and the BET is 120m 2 / g; the molar ratio of the reducing agent to the titanium in the precipitate is 1:0.9; the mixture is slurried with pure water to make a solid content of 35wt%, ground to a material particle size of 300nm, spray-dried to obtain a material with a particle size of 18.5μm and a moisture content of less than 1.5wt%, and calcined at 700°C for 9h while introducing nitrogen for protection to obtain a calcined material.
[0081] The calcined product was added into a sodium hydroxide solution with a concentration of 0.3 mol / L, and the mass ratio of the calcined product to the sodium hydroxide solution was 1:1.5. The product was steamed at 105°C for 20 min, and then filtered, washed and dried to obtain a lithium iron phosphate dopant. The SEM test showed that Figure 1 The performance test results are as follows:
[0082] Table 1 Detection results of lithium iron phosphate dopant obtained in Example 1
[0083] index Li Ti P F C data 10.46% 21.46% 29.11% 0.24% 3.15% BET PD Bulk density <![CDATA[Ti 4+ ]]> D10 D50 <![CDATA[25.6m 2 / g]]> 2.56g / mL 0.71g / mL 357ppm 0.4μm 1.5μm D90 pH Ca Mg Na Magnetic materials 8.9μm 11.3 56.7ppm 27.4ppm 67.4ppm 0.12ppm
[0084] Example 2
[0085] This embodiment provides a method for preparing a lithium iron phosphate dopant, which differs from the embodiment 1 only in that the molar ratio of the reducing agent to the titanium in the precipitate is 1:0.5. Specifically, the detection results of the obtained dopant are as follows:
[0086] Table 2 Detection results of lithium iron phosphate dopant obtained in Example 2
[0087] index Li Ti P F C data 10.02% 21.15% 28.96% 0.22% 4.58% BET PD Bulk density <![CDATA[Ti 4+ ]]> D10 D50 <![CDATA[29.6m 2 / g]]> 2.53g / mL 0.70g / mL 217ppm 0.4μm 1.4μm D90 pH Ca Mg Na Magnetic materials 9.3μm 11.5 52.9ppm 22.5ppm 64.9ppm 0.14ppm
[0088] Example 3
[0089] This embodiment provides a method for preparing a lithium iron phosphate dopant, which differs from Embodiment 1 only in that the molar ratio of the reducing agent to the titanium in the precipitate is 1:2. Specifically, the detection results of the obtained dopant are as follows:
[0090] Table 3 Test results of lithium iron phosphate dopant obtained in Example 3
[0091] index Li Ti P F C data 11.28% 22.69% 30.57% 0.29% 2.05% BET PD Bulk density <![CDATA[Ti 4+ ]]> D10 D50 <![CDATA[22.57m 2 / g]]> 2.52g / mL 0.75g / mL 529ppm 0.4μm 1.6μm D90 pH Ca Mg Na Magnetic materials 9.4μm 11.1 52.6ppm 23.8ppm 69.4ppm 0.11ppm
[0092] Example 4
[0093] This embodiment provides a method for preparing a lithium iron phosphate dopant, which is different from the embodiment 1 only in that the molar ratio of the precipitate, lithium phosphate, lithium carbonate, and lithium fluoride is 1:2.2:1.6:0.1. Specifically, the test results of the obtained dopant are as follows:
[0094] Table 4 Detection results of lithium iron phosphate dopant obtained in Example 4
[0095] index Li Ti P F C data 11.38% 21.01% 29.89% 0.31% 3.02% BET PD Bulk density <![CDATA[Ti 4+ ]]> D10 D50 <![CDATA[25.1m 2 / g]]> 2.52g / mL 0.68g / mL 328ppm 0.3μm 1.6μm D90 pH Ca Mg Na Magnetic materials 9.4μm 11.6 60.4ppm 29.5ppm 69.1ppm 0.11ppm
[0096] Example 5
[0097] This embodiment provides a method for preparing a lithium iron phosphate dopant, which differs from the embodiment 1 only in that the molar ratio of the precipitate, lithium phosphate, lithium carbonate, and lithium fluoride is 1:2.05:1.4:0.05. The test results of the dopant finally obtained are as follows:
[0098] Table 5 Test results of lithium iron phosphate dopant obtained in Example 5
[0099] index Li Ti P F C data 10.11% 22.16% 29.01% 0.16% 3.19% BET PD Bulk density <![CDATA[Ti 4+ ]]> D10 D50 <![CDATA[26.9m 2 / g]]> 2.57g / mL 0.72g / mL 365ppm 0.3μm 1.6μm D90 pH Ca Mg Na Magnetic materials 9.8μm 11.2 53.7ppm 26.2ppm 65.9ppm 0.13ppm
[0100] Example 6
[0101] This embodiment provides a method for preparing a lithium iron phosphate dopant, which differs from Embodiment 1 only in that the mass ratio of the calcined product to the sodium hydroxide solution is 1:1. Specifically, the test results of the obtained dopant are as follows:
[0102] Table 6 Test results of lithium iron phosphate dopant obtained in Example 6
[0103] index Li Ti P F C data 10.28% 23.36% 29.01% 0.21% 3.13% BET PD Bulk density <![CDATA[Ti 4+ ]]> D10 D50 <![CDATA[21.5m 2 / g]]> 2.61g / mL 0.78g / mL 348ppm 0.5μm 1.7μm D90 pH Ca Mg Na Magnetic materials 9.7μm 11.1 53.8ppm 24.9ppm 64.8ppm 0.11ppm
[0104] Example 7
[0105] This embodiment provides a method for preparing a lithium iron phosphate dopant, which differs from Embodiment 1 only in that the mass ratio of the calcined product to the sodium hydroxide solution is 1:2. Specifically, the test results of the obtained dopant are as follows:
[0106] Table 7 Test results of lithium iron phosphate dopant obtained in Example 7
[0107]
[0108]
[0109] Comparative Example 1
[0110] This comparative example provides a method for preparing a lithium iron phosphate dopant, which differs from Example 1 only in that no fluorine source is added. Specifically, the test results of the obtained dopant are as follows:
[0111] Table 8 Test results of lithium iron phosphate dopant obtained in Comparative Example 1
[0112] index Li Ti P F C data 10.31% 21.68% 29.29% 2.6ppm 3.21% BET PD Bulk density <![CDATA[Ti 4+ ]]> D10 D50 <![CDATA[24.5m 2 / g]]> 2.53g / mL 0.72g / mL 341ppm 0.5μm 1.6μm D90 pH Ca Mg Na Magnetic materials 9.7μm 11.2 54.2ppm 26.1ppm 65.1ppm 0.12ppm
[0113] Comparative Example 2
[0114] This comparative example provides a method for preparing a lithium iron phosphate dopant, which differs from Example 1 only in that no alkali solution is added to the calcined product for treatment. Specifically, the test results of the obtained dopant are as follows:
[0115] Table 9 Test results of lithium iron phosphate dopant obtained in Comparative Example 2
[0116] index Li Ti P F C data 10.35% 22.01% 29.28% 0.22% 3.19% BET PD Bulk density <![CDATA[Ti 4+ ]]> D10 D50 <![CDATA[12.5m 2 / g]]> 2.64g / mL 0.73g / mL 387ppm 0.3μm 1.7μm D90 pH Ca Mg Na Magnetic materials 14.7μm 11.2 54.1ppm 26.6ppm 65.2ppm 0.12ppm
[0117] Comparative Example 3
[0118] This comparative example provides a method for preparing a lithium iron phosphate dopant, which differs from Example 1 only in that an ammonium dihydrogen phosphate solution and an ammonium bicarbonate solution are added to the titanyl sulfate solution, and the pH of the solution is adjusted to 3.0. Specifically, the test results of the obtained dopant are as follows:
[0119] Table 10 Test results of lithium iron phosphate dopant obtained in comparative example 3
[0120] index Li Ti P F C data 11.02% 22.79% 25.81% 0.29% 3.18% BET PD Bulk density <![CDATA[Ti 4+ ]]> D10 D50 <![CDATA[23.7m 2 / g]]> 2.59g / mL 0.74g / mL 348ppm 0.3μm 1.7μm D90 pH Ca Mg Na Magnetic materials 10.3μm 11.2 55.5ppm 28.5ppm 68.9ppm 0.11ppm
[0121] The lithium iron phosphate dopant prepared in Examples 1-7 and Comparative Examples 1-3 was mixed with iron phosphate, lithium carbonate and glucose respectively, the mass ratio of dopant to iron phosphate, lithium carbonate and glucose was 0.05:1:0.235:0.165, pure water was added to slurry so that the solid content was 35wt%, ground to a slurry particle size of 300nm, spray dried so that the particle size of the material was 20μm and the moisture content was less than 1.5wt%, and then calcined at a temperature of 820°C under nitrogen protection for 9h to obtain a lithium iron phosphate positive electrode material. The test results are shown in Tables 11 to 20.
[0122] Table 11 Test results of lithium iron phosphate positive electrode materials prepared in Example 1
[0123]
[0124] Table 12 Test results of lithium iron phosphate positive electrode materials prepared in Example 2
[0125]
[0126] Table 13 Test results of lithium iron phosphate positive electrode materials prepared in Example 3
[0127]
[0128]
[0129] Table 14 Test results of lithium iron phosphate positive electrode materials prepared in Example 4
[0130]
[0131] Table 15 Test results of lithium iron phosphate positive electrode materials prepared in Example 5
[0132]
[0133] Table 16 Test results of lithium iron phosphate positive electrode materials prepared in Example 6
[0134]
[0135] Table 17 Test results of lithium iron phosphate positive electrode materials prepared in Example 7
[0136]
[0137]
[0138] Table 18 Test results of lithium iron phosphate positive electrode materials prepared in Comparative Example 1
[0139]
[0140] Table 19 Test results of lithium iron phosphate positive electrode materials prepared in comparative example 2
[0141]
[0142] Table 20 Test results of lithium iron phosphate positive electrode materials prepared in comparative example 3
[0143]
[0144] 2. Test Method
[0145] 1. Performance test of lithium iron phosphate dopant
[0146] (1) SEM test
[0147] The lithium iron phosphate dopant prepared in Example 1 was subjected to SEM detection using a MERLIN Compact field emission scanning electron microscope (model: Quanta200FEG) produced by Zeiss.
[0148] (2) Particle size test
[0149] The particle size of the lithium iron phosphate dopant prepared in the embodiment and the comparative example was tested by a laser particle size analyzer, with reference to the standard GB / T 24533-2019.
[0150] (3) BET test
[0151] The specific surface areas of the lithium iron phosphate dopants prepared in the examples and comparative examples were tested by nitrogen adsorption BET test method, with reference to standard GB / T 19587-2017.
[0152] (4) Elemental analysis
[0153] The metal element content in the lithium iron phosphate dopant prepared in the embodiment and the comparative example was tested by inductively coupled plasma emission spectroscopy, with reference to standard GB / T 33822-2017.
[0154] 2. Performance test of lithium iron phosphate cathode material
[0155] (1) BET test
[0156] The test was carried out using the nitrogen adsorption BET test method, with reference to the standard GB / T 19587-2017.
[0157] (2) Compaction density test
[0158] The test was carried out using a compaction density tester, with reference to the standard GB / T 24533-2019, where the test pressure was 3T.
[0159] (3) Capacity test
[0160] With reference to standard GB / T 33822-2017, the lithium iron phosphate positive electrode material was stirred with the conductive agent Super-P, the adhesive PVDF and NMP to prepare a slurry, the slurry was evenly coated on an aluminum foil and dried in an oven at 125°C to make an electrode sheet. The negative electrode sheet was made of metallic lithium sheet, and the electrolyte was 1 mol / L LiPF6 / (EC+DEC) mass ratio (1:1) to assemble a simulated battery for electrochemical performance testing.
[0161] III. Analysis of test results of various embodiments and comparative examples
[0162] from Figure 2 It can be seen that the lithium iron phosphate dopant particles prepared in the present application are spherical in shape, the particle distribution is relatively uniform, the surface is relatively smooth, there are no obvious cracks or pores, and the stability and consistency of the material can be maintained.
[0163] It can be seen from Tables 1 to 20 that the lithium iron phosphate dopant prepared by the method of the present application can increase the BET specific surface area and charge and discharge capacity of the lithium iron phosphate positive electrode material. It can be seen from Tables 11 and 18 that when preparing the lithium iron phosphate dopant in Comparative Example 1, no fluorine source was added, resulting in a decrease in the charge capacity and discharge capacity of the final lithium iron phosphate positive electrode material, and the -20°C capacity retention rate was only 70.2%. It can be seen from Tables 6, 7 and 9 that in Comparative Example 2, the calcined material was not treated with alkali solution, resulting in a significant decrease in the BET specific surface area of the prepared lithium iron phosphate dopant. It can be seen from Table 19 that the BET specific surface area of the final lithium iron phosphate positive electrode material is reduced, and the charge and discharge capacity and -20°C capacity retention rate are both reduced. From the comparison between Table 1 and Table 10, it can be seen that the increase in pH value in Comparative Example 3 leads to a wider particle size distribution of the prepared lithium iron phosphate dopant, indicating that the change in pH value will affect the crystal structure and particle morphology of the precipitate. At a lower pH value, it is easier to form small and regular particles, and a higher pH value leads to the formation of irregular particle shapes or agglomeration, which affects the electronic conductivity and ion diffusion properties of the material, resulting in a decrease in the charge and discharge performance of the lithium iron phosphate positive electrode material. Therefore, by adding the lithium iron phosphate dopant provided by the present application, a lithium iron phosphate positive electrode material with high capacity and excellent low temperature performance can be obtained.
[0164] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A method for preparing a lithium iron phosphate dopant, characterized in that: The following steps are involved: Adding a phosphate solution and an ammonium salt solution to a titanium salt solution, adjusting the pH value of the solution to 1.5-2.5, and obtaining a precipitate; adding a phosphorus source, a lithium source, a fluorine source and a reducing agent to the precipitate to obtain a mixture, and then sequentially subjecting the mixture to slurrying, dispersion, drying and calcination to obtain a calcined product; Alkaline solution is added to the calcined product, and the product is boiled, filtered, washed and dried to obtain a lithium iron phosphate dopant.
2. The method for preparing a lithium iron phosphate dopant according to claim 1, characterized in that: The concentrations of the titanium salt solution and the phosphate solution are both 1-2 mol / L; and / or The molar ratio of the titanium salt contained in the titanium salt solution to the phosphate contained in the phosphate solution is 3:(4.05-4.1).
3. The method for preparing the lithium iron phosphate dopant according to claim 2, characterized in that: The titanium salt contained in the titanium salt solution is at least one of titanyl sulfate and titanium tetrachloride; and / or The phosphate contained in the phosphate solution is one or more of ammonium phosphate, sodium phosphate, ammonium monohydrogen phosphate, sodium monohydrogen phosphate, ammonium dihydrogen phosphate and sodium dihydrogen phosphate.
4. The method for preparing a lithium iron phosphate dopant according to claim 2, characterized in that: The concentration of the ammonium salt solution is 0.1 to 1 mol / L; and / or The ammonium salt contained in the ammonium salt solution is at least one of ammonium carbonate and ammonium bicarbonate.
5. The method for preparing a lithium iron phosphate dopant according to claim 1, characterized in that: The molar ratio of the precipitate, the phosphorus source, the lithium source and the fluorine source is 1:(2.05-2.2):(1.4-1.6):(0.05-0.1); and / or The phosphorus source is at least one of lithium phosphate and lithium dihydrogen phosphate; and / or The lithium source is at least one of lithium carbonate and lithium hydroxide; and / or The fluorine source is lithium fluoride; and / or The molar ratio of the reducing agent to the titanium in the precipitate is 1:(0.5-2); and / or The reducing agent is at least one of carbon, oxalic acid, citric acid, ascorbic acid and glucose.
6. The method for preparing a lithium iron phosphate dopant according to claim 1, characterized in that: The slurrying method is: adding water to the mixture to slurry the mixture so that the solid content is 30-40wt%; and / or The dispersion method is: grinding the slurried material until the particle size of the material is 200 to 400 nm; and / or The drying method is: spray drying the ground material to obtain a dry material with a particle size of 5 to 25 μm and a moisture content of less than 1.5 wt%; and / or The calcination method is: calcining the dried material at 600-750° C. for 6-12 hours.
7. The method for preparing a lithium iron phosphate dopant according to claim 1, characterized in that: The alkali solution is one of potassium hydroxide solution, lithium hydroxide solution and sodium hydroxide solution, and the concentration is 0.1-0.5 mol / L; and / or The mass ratio of the calcined product to the alkali solution is 1:(1-2); and / or The cooking temperature is 100-110° C., and the cooking time is 15-30 minutes.
8. A lithium iron phosphate dopant, characterized in that: The lithium iron phosphate dopant is prepared by the preparation method of any one of claims 1 to 7, wherein the particle size of the lithium iron phosphate dopant is 0.5 to 5.0 μm, and the BET specific surface area is 20 to 30 m 2 / g.
9. A lithium iron phosphate positive electrode material, characterized in that: The lithium iron phosphate dopant according to claim 8 is prepared by solid phase reaction with iron phosphate, a lithium source and a carbon source.
10. A positive electrode sheet, characterized in that: Including the lithium iron phosphate positive electrode material as described in claim 9.